PENGARUH MOTIVASI, PENGEMBANGAN KARIR, DAN KEDISIPLINAN TERHADAP KINERJA PEGAWAI PADA BADAN PENELITIAN DAN PENGEMBANGAN INDUSTRI BALAI BESAR TEKNOLOGI PENCEGAHAN PENCEMARAN INDUSTRI - Ida Rosiana, 13.05.51.0054 (Students' Journal of Economic and Management, 2017)
This study aims to example and analyze the effect of motivation, career development and discipline to work on the performance of employees of Balai Besar Teknologi Pencegahan Pencemaran Industri (BBTPPI). The best data used in this study include the product moment test validity, realiability testing with Cronbach Alpha multiple linear regression analysis, t test to test and prove the research hypothesis.Data collected was tested for validity by the methods of analysis and tested reliabilitas with product moment coefficient alpha (Cronbach Alpha), where the results of all data is valid and reliable. The results of the analysis and discussion demonstrate that: (1). Motivation and significant positive effect on employee performance, the stronger the influence of the motivation, then the performance employee’s are also increasing; (2). Career development positive and significant effect on the performance of employees, the stronger the influence of the working career development, then the performance employee’s are also increasing; (3). Discipline positive and significant effect on the performance of employees, the stronger the influence of the working discipline, then the performance employee’s in the company are also increasing. Keywords :Motivation, Career Development, Discipline, Employee performance